All-organic electro-optic waveguide modulator comprising SU-8 and nonlinear optical polymer - Nitiss, Edgars; Tokmakovs, Andrejs; Pudzs, Kaspars; Busenbergs, Janis; Rutkis, Martins (OSA - The Optical Society, 2017)
In this paper we describe the principles of operation as well as the fabrication and testing steps of an all-organic waveguide modulator. The modulator comprises an SU-8 core and an electro-optic host-guest polymer cladding. The polymer properties are tuned in order to achieve single mode operation. We used direct-write laser lithography in two steps for the preparation of the devices. The electro-optic coefficient of the polymer is estimated from observing the modulation of the device operated in push-pull mode.
Institute of Solid State Physics, University of Latvia (SJZ/2016/26); Ministry of Education and Science, Republic of Latvia (MultIfunctional Materials and composItes, photonicS and nanotechnology (IMIS2)). We acknowledge Dr. Anatolijs Sarakovskis at Institute of Solid State Physics for the XPS measurements.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics